Ribonucleoprotein assembly defects correlate with spinal muscular atrophy severity and preferentially affect a subset of spliceosomal snRNPs. - Francesca Gabanella; Matthew E R Butchbach; Luciano Saieva; Claudia Carissimi; Arthur H M Burghes; Livio Pellizzoni (PLoS ONE)
Spinal muscular atrophy (SMA) is a motor neuron disease caused by reduced levels of the survival motor neuron (SMN) protein. SMN together with Gemins2-8 and unrip proteins form a macromolecular complex that functions in the assembly of small nuclear ribonucleoproteins (snRNPs) of both the major and the minor splicing pathways. It is not known whether the levels of spliceosomal snRNPs are decreased in SMA. Here we analyzed the consequence of SMN deficiency on snRNP metabolism in the spinal cord of mouse models of SMA with differing phenotypic severities. We demonstrate that the expression of a subset of Gemin proteins and snRNP assembly activity are dramatically reduced in the spinal cord of severe SMA mice. Comparative analysis of different tissues highlights a similar decrease in SMN levels and a strong impairment of snRNP assembly in tissues of severe SMA mice, although the defect appears smaller in kidney than in neural tissue. We further show that the extent of reduction in both Gemin proteins expression and snRNP assembly activity in the spinal cord of SMA mice correlates with disease severity. Remarkably, defective SMN complex function in snRNP assembly causes a significant decrease in the levels of a subset of snRNPs and preferentially affects the accumulation of U11 snRNP--a component of the minor spliceosome--in tissues of severe SMA mice. Thus, impairment of a ubiquitous function of SMN changes the snRNP profile of SMA tissues by unevenly altering the normal proportion of endogenous snRNPs. These findings are consistent with the hypothesis that SMN deficiency affects the splicing machinery and in particular the minor splicing pathway of a rare class of introns in SMA.